2021
DOI: 10.2478/eoik-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Macroeconomic Aggregates of the European Union

Abstract: Economic experts’ predictions of a slowdown in the EU’s global economy and economic growth in the year 2020 were based on various risks and uncertainties existing on a world scale, ranging from the US-China trade war, traditionally strained relations of the EU and the US on the one hand and the Russian Federation on the other, all the way to BREXIT and economic migration to developed EU countries. However, the COVID-19 pandemic has further aggravated those forecasts, so that the entire EU is recording a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The pandemic caused by the COVID-19 virus has shown that medical facilities must put focus on HCW management. This pandemic affected all spheres of life ( Đukić et al, 2021 ). Different measures have been taken to prevent the spread of the COVID-19 virus.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic caused by the COVID-19 virus has shown that medical facilities must put focus on HCW management. This pandemic affected all spheres of life ( Đukić et al, 2021 ). Different measures have been taken to prevent the spread of the COVID-19 virus.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID 2019 pandemic, which struck the EU in early 2020, demonstrated how nonfinancial and non-economic factors can affect economic trends and the economy on a global scale and cause a recession at that. In the same way and with much greater effects, the crisis reflected on small open economies such as the Republika Srpska (Đukić A., Štaka M., Drašković D. 2021). The impact of the COVID 19 crisis on the fiscal stability of the Republika Srpska is analyzed, ie the impact of the crisis on the enormous growth of the deficit and the measures for its reduction to the framework defined by the Law.…”
Section: Research Methodology and Methodsmentioning
confidence: 99%
“…Te COVID-19 pandemic that has been characterized as an economic crisis [9], which has afected the whole world since March 2020, has been showing its efects on operations and supply chains around the world in a way that is difcult to model, measure, and predict. To stop the disease from spreading in the absence of vaccines, governments have taken nonpharmacological interventions (such as social distance policies and civil lockdowns) around the world and tried to limit human mobility.…”
Section: Introductionmentioning
confidence: 99%